The underlying mechanism and targeted therapy strategy of miRNAs cross-regulating EMT process through multiple signaling pathways in hepatocellular carcinoma - Chen, Juan; He, Fuguo; Peng, Hong; Guo, Jinjun (Frontiers in Molecular Biosciences, 2024)
The consistent notion holds that hepatocellular carcinomahepatocellular carcinoma (HCC) initiation, progression, and clinical treatment failure treatment failure are affected by the accumulation of various genetic and epigenetic alterations. Early research on the molecular mechanisms of hepatocarcinogenesis focused on proteincoding genes, this is own to that proteins are often regarded as central to molecular biology. With in-depth research, accumulating evidence suggests that microRNAs (miRNAs) play an irreplaceable role in a variety of physical and pathological conditions. Especially, MicroRNAs (miRNAs) play an irreplaceable role in a variety of physiological and pathological states. meanwhile, epithelial-mesenchymal transition (EMT) is a crucial biological process that controls the development of HCC. miRNAs regulate the intermediation state of epithelial-mesenchymal transition (EMT) or mesenchymal-epithelial transition (MTE) thereby regulating HCC progression.to finetune the HCC process. Notably, miRNAs regulate key HCC-related molecular pathways, including the Wnt/β-catenin pathway, PTEN/PI3K/AKT pathway, TGF-β pathway, and RAS/MAPK pathway. Therefore, we comprehensively reviewed how miRNAs produce EMT effects by multiple signaling pathways and their potential significance in the pathogenesis and treatment response of HCC. Therefore, we reviewed the effects of EMT effect-mediated miRNAs on multiple pathways of HCC molecular mechanisms and their potential implications in HCC pathogenesis and response to therapy. emphasizing their molecular pathways and progression in HCC initiation. Additionally, we also pay attention to regulatory mechanisms that are partially independent of signaling pathways. Finally, we summarize and propose miRNA-targeted therapy and diagnosis and defense strategies for HCChepatocellular 设置了格式: 字体: (默认) Times New Roman, (中文) Times New Roman carcinoma. Shortly, Tthe identification of the mechanism leading to the activation of EMT programs during HCC disease processes also provides a new protocol for the plasticity of distinct cellular phenotypes and possible therapeutic interventions.Likewise, the biological significance and clinical application of miRNAs in HCC are involved to provide new directions and thoughts for subsequent research.ConsequentlyThus, we summarize the latest progress in this direction, with a promising path for further insight into this fast-moving field.